Проблема національної ідентичності та творчої індивідуальності у прозових текстах Василя Стуса і Чеслава Мілоша - Михайлова, Т. (Слово і Час, 2022)
У статті на прикладі самвидавних текстів української і польської літератур, зокрема есею Чеслава Мілоша «Альфа, або Мораліст» із книжки
«Поневолений розум» і літературно-критичної розвідки Василя Стуса
«Феномен доби (Сходження на Голгофу слави)», у типологічному аспекті
розглянуто проблему збереження / втрати письменником власної індивідуальності, важливим складником якої є національна ідентичність. У контексті тоталітарної системи, котра вбачала в мистецтві спосіб утвердження ідеології, проаналізовано особливості зображення Ч. Мілошем і В. Стусом своїх відомих сучасників — прозаїка Єжи Анджеєвського і поета
Павла Тичини відповідно. Зіставлено мотив перевдягання і вдавання із себе
Іншого, окреслено риси творчості на догоду владі як свідоме відступництво
від власного «Я». Порівняння обох текстів дає змогу простежити, як виконання ролі державного письменника веде до знищення індивідуальності, а з нею і національної ідентичності, перетворюючи митця на «мертву» людину-функцію. In a typological way, the paper considers the problem of preservation/loss of the writer’s
individuality, with a focus on the national identity as its essential component, on the example
of the self-published texts of Ukrainian and Polish literature, in particular the essay
by Czesław Miłosz “Alpha, or Moralist” from the book “The Captive Mind” and literarycritical
research work by Vasyl Stus “Phenomenon of the Age (Ascent to Calvary of Glory)”.
Both for Vasyl Stus and Czesław Miłosz the native language is a matter of special importance
as well as their attachment to the homeland, which is expressed in the awareness of the
impossibility to fully realize their talents abroad. In the context of the totalitarian system,
which perceived art as a means of asserting ideology, the paper analyzes image features of a
famous prose writer Jerzy Andrzejewski and outstanding poet Pavlo Tychyna in the texts of
their contemporaries Cz. Miłosz and V. Stus. The main issues are the motive of disguise and
pretending to be another, the peculiarities of creative work aiming at pleasing the authorities
as a conscious apostasy from one’s own “I”. The role of a state writer leads to the destruction
of the writer’s individuality, in particular his national identity (in the “Phenomenon of the
Age”), turning the artist into a ‘dead’ person-function. V. Stus and Cz. Miłosz are similar in
their desire to understand the writers represented in their texts, to interpret them as victims
of the system. Attention is drawn to the difference in the narration of the compared texts:
if Cz. Miłosz presents the story about J. Andrzejewski keeping some emotional distance,
V. Stus is deeply concerned about the loss of P. Tychyna’s poetic individuality, and with it –
national identity, perceiving the tragedy of Ukrainian literature as personal harm. The question
of national identity in the work by Cz. Miłosz is not actually raised, while in V. Stus’s
one it is presented quite clearly in its historical continuity as a fundamental problem of the
Ukrainian culture.